2016
DOI: 10.1002/eap.1416
|View full text |Cite
|
Sign up to set email alerts
|

Potential breeding distributions of U.S. birds predicted with both short‐term variability and long‐term average climate data

Abstract: Climate conditions, such as temperature or precipitation, averaged over several decades strongly affect species distributions, as evidenced by experimental results and a plethora of models demonstrating statistical relations between species occurrences and long-term climate averages. However, long-term averages can conceal climate changes that have occurred in recent decades and may not capture actual species occurrence well because the distributions of species, especially at the edges of their range, are typi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 70 publications
3
37
0
Order By: Relevance
“…Across species, EXT and COMP models tended to predict more restrictive suitable ranges than AVG models suggesting that extreme weather conditions might limit species distributions in areas theoretically suitable in terms of long‐term mean climatic conditions. In other words, models based on long‐term averages might be over predicting the amount of environmental suitable area for a species, at least in some areas (Zimmermann et al , Reside et al , Bateman et al , , Briscoe et al ). Divergences between model predictions showed strong patterns in geographic and environmental space (Supplementary material Appendix 7), providing general insight into key processes that may be missed by failing to consider a broad suite of climate variables.…”
Section: Discussionmentioning
confidence: 99%
“…Across species, EXT and COMP models tended to predict more restrictive suitable ranges than AVG models suggesting that extreme weather conditions might limit species distributions in areas theoretically suitable in terms of long‐term mean climatic conditions. In other words, models based on long‐term averages might be over predicting the amount of environmental suitable area for a species, at least in some areas (Zimmermann et al , Reside et al , Bateman et al , , Briscoe et al ). Divergences between model predictions showed strong patterns in geographic and environmental space (Supplementary material Appendix 7), providing general insight into key processes that may be missed by failing to consider a broad suite of climate variables.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also tended to focus on raw climatic variables to assess bird responses to precipitation variability (e.g., Bateman et al, 2016;Illán et al, 2014). However, using metrics that more comprehensively capture deviations from average moisture conditions, such as the Standardized Precipitation Evapotranspiration Index ("SPEI"), may also reveal important patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Drivers also act across a range of temporal scales, often concurrently, and may produce lagged responses at the population level. For example, climatic episodes such as the El Niño Southern Oscillation influence weather patterns over broad spatial and temporal scales (Stenseth et al 2003) and have been shown to affect demographic rates (Nott et al 2002, Lamanna et al 2012), long-term population trajectories, and resultant species distributions (Luoto et al 2007, Bateman et al 2016…”
Section: Understanding Population Processesmentioning
confidence: 99%